THE TRADITION OF THE LOM BADA LONG ISLAND COMMUNITIES IN FISHERIES RESOURCES UTILIZATION OF COUNTRY AIR BANGIS RIVER SUB SUNGAI BEREMAS DISTRICT WEST PASAMAN PROVINCE WEST SUMATERA - Ridho Nurhidayat; Kusai Kusai; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract          This research has been conducted in May 2018 in Air Bangis Country, Sungai Beremas River Sub, Pasaman Barat District, West Sumatera Province. This study aim to describe the practice of tradition Lom Bada Long Island community and analyze the benefits of Lom Bada tradition management system at Long Island Village, Air Bangis country. The methods used in this research is qualitative method with the fenomelogis approach, the determination of the sampling technique using information from a variety of sources.          The kind of tradition that has been carried out Long Island Village country community Air Bangis i.e 1. Any result of the income of fishermen left to sysop Lom Bada as much as 5%, 2. This tradition has been carried out since the year 1955 to the present, 4. There are values and awareness 4. There are norms of religious norms, manners, customs and norms of moral value built since yore hereditary to build the caracter of society of the importance of maintaining traditions that have existed in Jorong Long Island. Keywords: Tradition, Lom Bada,Norms, Society, Fisherman, Moral, Long Island, Air Bangis